2018
DOI: 10.1186/s13570-018-0120-x
|View full text |Cite
|
Sign up to set email alerts
|

Managing livelihood risks: Income diversification and the livelihood strategies of households in pastoral settlements in Isiolo County, Kenya

Abstract: Research in northern Kenya presents evidence that livestock herding remains the most important income activity for households in pastoral settlements, even though non-livestock income activities constitute a significant proportion of household income. This paper explores the socio-economic determinants of pastoral income diversification using rural household data collected from three pastoral settlement in Isiolo County, northern Kenya. This study is concerned with the patterns and determinants of participatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 72 publications
1
14
0
Order By: Relevance
“…Pastoral peoples in Africa, and many areas around the world, have been diversifying their economies since time millennial [ 79 ]. There are many records of where this option has worked, such as the Maasai in northern Tanzania [ 79 , 80 ], Kenya [ 81 ] and Ethiopia [ 82 , 83 ]. Ayeri [ 17 ], suggested that the adaptive capacity of pastoralists can be improved if national policies promote coping or adaptation approaches that are already being employed by pastoralists in their communities.…”
Section: Discussionmentioning
confidence: 99%
“…Pastoral peoples in Africa, and many areas around the world, have been diversifying their economies since time millennial [ 79 ]. There are many records of where this option has worked, such as the Maasai in northern Tanzania [ 79 , 80 ], Kenya [ 81 ] and Ethiopia [ 82 , 83 ]. Ayeri [ 17 ], suggested that the adaptive capacity of pastoralists can be improved if national policies promote coping or adaptation approaches that are already being employed by pastoralists in their communities.…”
Section: Discussionmentioning
confidence: 99%
“…However, traders in Teso who pursued this strategy did report more difficulty in re-engaging in cattle trade once the lockdown was lifted. Karamojong traders could not easily diversify because they have a low asset base, are dependent mainly on livestock, and crop farming is not their main livelihood (Achiba 2018 ; McCabe et al 2010 ; McCabe et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…As livestock is the main source of livelihood for a majority of the populations of the arid counties (16, 15,13,14,24], both levels of Government require to apply strategies that provide the most benefits to the nomadic livestock-keepers who are among the most vulnerable segment of the population of the arid lands, similar to the elderly, children, widowers and widows in the urban centres. Strategies with the potential for reducing the vulnerability of the nomadic pastoralists include: diversifying survival strategies that support pastoralism [25], subsidizing the growing and supply of fodder crops and hay, with stubble being available for animal grazing after harvest, and increasing and designating water points for livestock [26]; Value-added diversification of the products of the livestock and complimentary sectors, and ensuring that there are functioning mechanisms to keep more of the value within pastoralist areas should be encouraged [27]. Some animal by-products that are amenable to value-addition include hides, hooves, horns, bone, animal manure, fish scales, skins and gelatin, etc.…”
Section: General Food Production In Countiesmentioning
confidence: 99%